Disease-modifying therapies for Parkinson's disease - Sherer, Todd (Henry Stewart Talks, 2013)
The need for disease-modifying therapies for Parkinson's disease, Promising targets and pathways, Genetics, Neurorestoration, Implicated biochemical pathways, Challenges for clinical translation and testing, Need for Biomarkers, The Parkinson's Progression Markers Initiative